Alginate-enabled green synthesis of S/Ag1.93S nanoparticles, their photothermal property and in-vitro assessment of their anti-skin-cancer effects augmented by a NIR laser - Wei, Chuen Yoong; Chui, Fung Loke; Joon, Ching Juan; Yusoff, Khatijah; Mohtarrudin, Norhafizah; Tatsuma, Tetsu; Ying, Xu; Teck, Hock Lim (Elsevier, 2022)
We report herein the design and synthesis of colloidally-stable S/Ag1.93S nanoparticles, their photothermal conversion properties and in vitro cytotoxicity toward A431 skin cancer cells under the excitation of a minimally-invasive 980 nm near-infrared (NIR) laser. Micron-sized S particles were first synthesized via acidifying Na2S2O3 using biocompatible sodium alginate as a surfactant. In the presence of AgNO3 and under rapid microwave-induced heating, alginate reduced AgNO3 to nascent Ag which reacted with molten S in situ forming S/Ag1.93S nanoparticles. The nanoparticles were characterized using a combination of X-ray diffraction, electron microscopies, elemental analysis, zeta-potential analysis and UV–VIS-NIR spectroscopy. The average particles size was controlled between 40 and 60 nm by fixing the mole ratio of Ag+:S2O32−. When excited by a 980 nm laser, S/Ag1.93S nanoparticles (~40 nm) produced with the least amount of AgNO3 exhibited a respectable photothermal conversion efficiency of circa 62% with the test aqueous solution heated to a hyperthermia-inducing 52 °C in 15 min. At 0.7 W/cm2, the viability of A431 skin cancer cells incubated with 7.0 ± 0.2 μg/mL of S/Ag1.93S nanoparticles reduced to 14 ± 0.6%, while an A431 cell control maintained an 80% cell viability. These results suggested that S/Ag1.93S nanoparticles may have good potential in reducing metastatic skin carcinoma.